2022
DOI: 10.3390/ijms23105634
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sodium-Glucose Co-Transporter 2 Inhibitors in the Regulation of Inflammatory Processes in Animal Models

Abstract: Sodium-glucose co-transporter 2 inhibitors, also known as gliflozins, were developed as a novel class of anti-diabetic agents that promote glycosuria through the prevention of glucose reabsorption in the proximal tubule by sodium-glucose co-transporter 2. Beyond the regulation of glucose homeostasis, they resulted as being effective in different clinical trials in patients with heart failure, showing a strong cardio-renal protective effect in diabetic, but also in non-diabetic patients, which highlights the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 223 publications
2
24
0
Order By: Relevance
“…The antidiabetic effects of SGLT2 inhibitors rely on the inhibition of renal reabsorption of glucose, but anti-inflammatory effects have also been reported including attenuation of IL-6 production37 and modulation of macrophage polarisation 38. The prospect of using the anti-inflammatory potential of SGLT2 inhibitors in various pathologies is currently receiving much attention 39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antidiabetic effects of SGLT2 inhibitors rely on the inhibition of renal reabsorption of glucose, but anti-inflammatory effects have also been reported including attenuation of IL-6 production37 and modulation of macrophage polarisation 38. The prospect of using the anti-inflammatory potential of SGLT2 inhibitors in various pathologies is currently receiving much attention 39…”
Section: Discussionmentioning
confidence: 99%
“…38 The prospect of using the anti-inflammatory potential of SGLT2 inhibitors in various pathologies is currently receiving much attention. 39 Additional subgroups Apart from obesity, hyperglycaemia and sex, other factors such as current smoking status and specific medical therapy may likewise influence the level of inflammation in type two diabetes. 40 41 In our cohort, only 5% were smokers, which is surprisingly low, giving the fact that smoking is a substantial risk factor for development of type 2 diabetes.…”
Section: Open Accessmentioning
confidence: 99%
“…In recent years, a hypothesis that has gained strength describes that beneficial action of SGLT2i on HF is due to a systemic effect [ 5 ]. SGLT2i could act as modulators of metabolic fuel used by the myocardium, specifically reducing glucose consumption and increasing the use of ketone bodies, which ameliorate adverse left ventricle remodeling [ 25 , 26 ]. Previously, we observed alterations in lipids metabolism in HF patients [ 27 ], as well as in animal models treated with empagliflozin [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors are not completely selective for SGLT2 and inhibit SGLT1 to different degrees. However, they are commonly referred to as SGLT2 inhibitors because their affinity for SGLT2 is considerably higher than for SGLT1 [ 48 ]. Although SGLT2 inhibition raises concerns about the risk of hypoglycemia, previous studies reported that SGLT2 inhibition increased glucose loading to the late proximal tubules, enhanced the glucose transport capacity of SGLT1, and limited glucose excretion and the risk of hypoglycemia.…”
Section: Renal Glucosuria In Humansmentioning
confidence: 99%